Nutrient timing for peak performance - Skolnik, Heidi 1961-; Chernus, Andrea 1957- (Champaign, IL Human Kinetics, 2010)
Gain the ultimate advantage! Nutrient Timing for Peak Performance is your guide to consuming the right foods at the right time for optimal results in training or competition. Renowned sport nutritionists Heidi Skolnik and Andrea Chernus have worked alongside today's top athletes, including professional football players and elite marathoners. In Nutrient Timing for Peak Performance, they've combined the latest dietetic research with practical advice you can use to create a personalized action plan based on the needs of your body, your sport, and your goals. With guidelines specific to training and competition, as well as sample meal and snack plans, you'll see how certain nutrients in precise amounts at specific times can improve consistency of energy, speed recovery, increase the building effects of strength training, diminish muscle breakdown, improve immune function, and minimize your risk of injury. Whether you are a dedicated triathlete, high school pitcher, college swimmer, competitive powerlifter, or professional soccer player, Nutrient Timing for Peak Performance is your guide to peak athletic training and performance.
Preface -- Part I. The Principles -- Chapter 1. The Nutrient Timing Advantage -- Chapter 2. The Science Made Simple -- Part II. The Nutrients -- Chapter 3. Carbohydrate as the Primary Fuel -- Chapter 4. The Protein Profile -- Chapter 5. Smart Fat in the Diet -- Chapter 6. Essential Vitamins and Minerals -- Chapter 7. The Role of Fluids -- Chapter 8. The Supplement Factor -- Part III. Fueling Strategies, Plans, and Menus -- Chapter 9. Timing Guidelines for Athletes -- Chapter 10. Strength and Power -- Chapter 11. Endurance -- Chapter 12. Stop and Go -- Appendixes -- Index -- About the Authors.
Includes bibliographical references
Keywords: Athletes -- Nutrition